Scientometric assessment of publishing patterns of agricultural researchers in the Slovenian national journals as indexed by the national online bibliographic database COBISS/COBIB - Tomaž BARTOL; Karmen STOPAR (Acta Agriculturae Slovenica)
The aim was to systematically analyze the patterns of scatter of both scientific and non-scientific articles by the scientists of the Agronomy, Biology, Food Science and Technology, Forestry, Wood Science and Technology, and the Zootechnical Departments of the Biotechnical Faculty of the University of Ljubljana in the Slovenian national journals in the period 1995-2002. The national online catalogue and bibliographic databases COBISS/ COBIB were employed to this end. Two experimental databases were set up to upload the data for further analysis. 240 different journals that published 4163 different articles were identified. 3141 Scientific and 1022 non-scientific articles were published in 82 and 203 journals respectively. 45 journals published both scientific and non-scientific articles. 12 journals published more than 100 articles each, and 78 different journals published a single article. The five core journals published 39% of all articles. This is an assessment of the national serial productivity and does not reflect the total scientific productivity as many authors may publish mainly in international periodicals which were not the object of this analysis. The main difficulties of this kind of study were presented in establishing a uniform group of authors. COBIB can be used to some extent but with limitations as a lot of manual editing is needed to extract the relevant data into a consistent group of articles for further analysis.